Faktor Penentu Kepuasan dan Loyalitas Pelanggan : Tinjauan Sistematis atas Kualitas Layanan, Citra Merek, dan Persepsi Harga - Intan Zayyinatun Nisa; Husnul Hotimah; Ahmad Riskillah Hamdani; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Customer satisfaction is a central issue in marketing management, as it plays a crucial role in determining customer loyalty amid increasingly intense business competition. A comprehensive understanding of the factors influencing customer satisfaction is essential not only for academics in strengthening marketing theory but also for practitioners in designing effective service and product strategies. This article aims to address two research questions: (1) what are the dominant factors influencing customer satisfaction, and (2) how does customer satisfaction relate to customer loyalty? The study employed a qualitative literature review method. The data consisted of scientific articles published between 2020 and 2025, accessed through Google Scholar and Publish or Perish (PoP) using the keyword “customer satisfaction.” From an initial selection of 30 articles, 27 were identified as relevant, and 5 core articles were further analyzed. The findings reveal three main themes: product and service quality as the dominant determinants of customer satisfaction; price, brand image, and promotion as supporting factors; and customer trust as an important mediating variable in building loyalty. This study concludes that customer satisfaction serves as a strategic link between service quality and customer loyalty. Future research is encouraged to explore the roles of digitalization, customer experience, and sustainability in shaping long-term customer satisfaction.